ANALISIS HUKUM TENTANG PENYELESAIAN SENGKETA TANAH SECARA MEDIAS OLEH KANTOR PERTANAHAN KOTA GORONTALO - Muh Nasir (AkMen JURNAL ILMIAH, 2016)
One of the natural resources or natural resources created by God Almighty that is necessary for human life is the ground. Humans live on the land and obtain food by utilizing the land. Human life can not be separated from land. The emergence of a legal dispute is originated from the mind of the guidance of a land rights to the status of land, priority or ownership with a hope to get administrative settlement in accordance with applicable regulations. Formulation of the problem in this research is how the role of the Land Office in the framework of land mediation Resolving Disputes in State Land Office Gorontalo.Faktor which impede the implementation of mediation in land disputes. What are the obstacles in the implementation of the Mediation. The method used is empirical juridical approach. Empirical jurisdiction, is a study in addition to seeing the positive aspects of the law also look at the implementation or practice in the field in this case the approach used to analyze qualitatively land dispute resolution by mediation in the Office of the city of Gorontalo. From the research that as a mediator, Office of Gorontalo City has a role in helping the parties to understand each other's views and to help find things that are important to them. Mediators facilitate the exchange of information, promote discussion about the differences of interest, perception, interpretation of situations and problems and regulate expression of emotion. Implementation of land dispute resolution through mediation by BPN needs to be grounded in the capacities authorized by legislation. Lack of sanctions legislation that affects the legal protection of land owners and the community at large, and therefore with reference to the concept of the theory of criminalization, particularly related to the purpose of criminal law is intended that any criminal laws aimed at tackling crime for the sake of people's welfare of its members